A REVİEW OF RESEARCH ON STEREOTYPES AND PREJUDİCE (Third Sector Social Economic Review, 2024)
In this study, it was aimed to examine the research articles on stereotypes and prejudice scanned in the social sciences category of the Scopus database by bibliometric analysis method. First, the criteria for the studies to be included in the study were applied in the Scopus database and data from 6057 studies were accessed. Data were analyzed with VOSviewer package program. First of all, the distribution of articles related to the research area over the years was analyzed. In the bibliometric analysis section, citation analysis, co-author analysis, co-citation analysis and keyword analysis were performed. When the distribution of articles according to years is examined, it is seen that studies on stereotypes and prejudice in general tend to increase. ""Journal of Educational Psychology"" and ""Social Science and Medicine"" journals have the highest number of articles. The result of the keyword analysis shows that there is a very rich field of study on stereotypes and prejudice. In addition to the Scopus database, further studies using other databases may contribute to the field. In addition to the articles analyzed in this study, other types of documents can be analyzed. Trends in stereotypes and prejudice can be specifically revealed by restricting the year of the research topic.
Keywords: Stereotype; prejudice; bibliometric analysis; scopus; scientific map analysis